3D mode shapes characterisation using phase-based motion magnification in large structures using stereoscopic DIC. (August 2018) - Molina-Viedma, A.J.; Felipe-Sesé, L.; López-Alba, E.; Díaz, F.A.
Highlights: Motion magnification was applied for first time to perform 3D DIC. Mode shapes of simple and complex shape elements were determined. FEM models validates the employment of motion magnification in stereoscopic systems. No aberration or incompatibility between sets of magnified images were observed. Magnification solves the measurement of small periodic displacements with 3D-DIC. Abstract: Phase-based motion magnification has been proposed as an effective methodology to visualise Operational Deflection Shapes (ODSs) using a single camera. In recent work, magnification allowed the observation of these ODSs by naked eye or more advanced measurements on magnified images by using 2D Digital Image Correlation (DIC). The combination of a full-field optical technique and motion magnification shows a high potential improving DIC measurement and providing qualitative and quantitative information for the interpretation of ODSs. However, both motion magnification and the combination with 2D-DIC is limited to a few cases where plane elements experiences in-plane motion, mainly beam-like structures. In order to provide a more general application, in this study measurements on couples of magnified images using stereoscopic 3D-DIC were performed. A cantilever beam was employed for validation purposes, comparing the results with numerical models. Afterwards, a measurement application on a large curved panel was carried out to show full capabilities of the proposed methodology for 3D characterisation. Visualisation in slow-motion video format enables an intuitive understanding of the deformation. The adopted methodology demonstrates to be highly useful in low amplitude tests, involving the use of little exciters or high frequency applications.